The Sandwiched Young Adults: How Do They Cope with Stress? - Amalina, Annisa'i Salma Nur; Abidin, Zainal (Psikostudia : Jurnal Psikologi, 2025)
This study aims to describe the coping strategies of sandwich generation individuals. The sandwich generation is defined as adult individuals who are responsible for being caregivers for their nuclear family and their aging parents. Individuals in early adulthood can also bear the role of the sandwich generation. Challenges faced by the individual sandwich generation related to their condition can have a negative impact on their psychological condition, including stress. This study uses phenomenological qualitative methods to gather the coping strategies of the sandwich generation individuals, especially those in early adulthood (ranging from 18 years to 39 years). Data are collected by phone interviews, conducted in a semi-structured manner. The analysis technique used in this research is thematic analysis. The results obtained from this study shows that each subject displayed various forms of coping strategies, including active coping, planning, suppression of competing activities, seeking social support for instrumental reasons, seeking social support for emotional reasons, positive reinterpretation and growth, acceptance, turning to religion, and focusing on and venting of emotions. Penelitian ini bertujuan untuk menggali gambaran strategi koping individu generasi sandwich. Individu generasi sandwich yakni individu dewasa yang telah berkeluarga dan merawat keluarga intinya, sekaligus bertanggung jawab untuk merawat orang tua atau mertua yang telah menua. Kondisi generasi sandwich juga dapat dialami oleh individu usia dewasa awal yang baru merintis kehidupan berkeluarga. Tantangan sebagai individu generasi sandwich yang dapat berdampak negatif terhadap kondisi psikologis individu, termasuk stres. Penelitian ini menggunakan metode kualitatif fenomenologi untuk mendapatkan gambaran strategi koping individu generasi sandwich, khususnya yang berusia dewasa awal (mulai dari 18 tahun hingga 39 tahun). Pengumpulan data dilakukan dengan wawancara melalui telepon secara semi-terstruktur. Data kemudian dianalisis secara tematik sehingga didapatkan gambaran bentuk-bentuk strategi koping yang dilakukan oleh individu generasi sandwich usia dewasa awal. Hasil yang didapatkan dari penelitian ini, strategi koping yang dilakukan individu mencakup active coping, planning, suppression of competing activities, seeking social support for instrumental reasons, seeking social support for emotional reasons, positive reinterpretation and growth, acceptance, turning to religion, dan focusing on and venting of emotions.